Perceptions of physiotherapists about their role in health promotion at an acute hospital: a qualitative study. Issue 2 (June 2015) - Walkeden, S.; Walker, K.M.
Abstract: Objective: To investigate the perceptions of physiotherapists about their role in health promotion in an acute inpatient setting. Design: Qualitative design using focus groups within a constructivist framework. Focus groups were recorded, transcribed verbatim and analysed using a constant comparative method. Setting: An acute National Health Service (NHS) hospital trust. Participants: Three focus groups were conducted with a total of 22 physiotherapists who were recruited purposively from the medical and surgical unit of the study hospital. Findings: Participants generally perceived health promotion to be within their scope of practice, particularly in relation to the promotion of physical activity and smoking cessation. Whilst some facilitators to engaging in health promotion were discussed, a large number of barriers to routine engagement in health promotion were identified. These included time constraints, the focus of acute settings on discharge, and scepticism of effectiveness. Conclusion: Pre- and postregistration physiotherapy education as well as mandatory training in NHS trusts should be reviewed to equip the workforce to engage in this crucial area of health care.